(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The role and place of administrative-territorial reform in the state policy of Kyrgyzstan are considered, initially as a pilot project, and subsequently on a national scale. Positive aspects of this reform of the leadership of Kyrgyzstan, as well as the opinions of scientists and experts in the field of general reform carried out in the country. Reviews and reports of journalists and the perception of the people of Kyrgyzstan. The time has come to carry out administrative-territorial reform in Kyrgyzstan, since from the moment of sovereignty in the country the time has come for reform not only in the administrative-territorial sector, but also in all spheres of public administration of the Kyrgyz Republic. The article examines the research of the said reform on a national scale, where elections of deputies to local keneshes (councils) have already been held. The results of the elections held on November 17, 2024 are analyzed and assessed. Currently, the issues of conducting administrative-territorial reform are widely discussed in the media, debates are held in both narrow and broad formats. Scientists and experts are also involved in the discussion. Today, it must be admitted, there are issues in terms of the lack of scientific research, monitoring and evaluation of materials for conducting administrative-territorial reform.